2015
DOI: 10.2115/fiber.71.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Take-Up Velocity on the Higher-Order Structure of the Melt-Electrospun PLLA/PDLA Blend Fibers

Abstract: The higher-order structure and the formations of SC and HC of the PLLA/PDLA blend melt-electrospun fibers collected on a rotating target were investigated. The diameter of the fiber decreased and the orientation factor increased with increasing take-up velocity. The formation of SC was promoted with decreasing fiber diameter and with increasing take-up velocity. The fiber collected on the fixed target was amorphous and did not show the molecular orientation to any particular directions indicating that the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…That phenomenon can be explained by jet stretching during spinning due to increased Coulombic repulsion between charges . Besides PE-PCF, PLA ST-PCF prepared through single-nozzle electrospinning demonstrated a similar trend, ,,, in which the diameters of PLA PCFs were originally 800–1400 nm and reduced to a range of 400–970 nm when the absolute value of applied voltage was increased from 12 to 25 kV . In addition, the study indicated the amount of crystals in ST-PCF could also be influenced by the applied voltage.…”
Section: Fabrication Technologiesmentioning
confidence: 85%
See 2 more Smart Citations
“…That phenomenon can be explained by jet stretching during spinning due to increased Coulombic repulsion between charges . Besides PE-PCF, PLA ST-PCF prepared through single-nozzle electrospinning demonstrated a similar trend, ,,, in which the diameters of PLA PCFs were originally 800–1400 nm and reduced to a range of 400–970 nm when the absolute value of applied voltage was increased from 12 to 25 kV . In addition, the study indicated the amount of crystals in ST-PCF could also be influenced by the applied voltage.…”
Section: Fabrication Technologiesmentioning
confidence: 85%
“…Another work showed that the PLA ST-PCF obtained by melt spinning presented greater thermostability than pure PLA, with a crystalline structure tunable through annealing process, enabling its usage in commodity fields as an engineering material . Thus, the thermal resistance and/or mechanical properties of ST-PCF can be tuned through choice of preparation method, which broaden the practical applications of PLA fibers. , …”
Section: Classification Of Pcfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the stretching and orientation of the macromolecular chains caused by high voltage during the electrospinning process can enhance the orientation of the macromolecular chains and promote the formation of sc-crystallites. Additionally, a drawing force induced by the electric field could increase the specific surface area of the molecular chain and enhance the interaction between the PLLA and PDLA chains, resulting in rapid crystallization of sc-crystallites (Yamamoto et al, 2015).…”
Section: Thermal Propertiesmentioning
confidence: 99%